2020
DOI: 10.1021/acs.joc.9b03180
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Rh-Catalyzed C-7 and C-6 Dual C–H Functionalization of Indolines: Synthesis of Functionalized Pyrrolocarbazoles

Abstract: A site-selective dual C-7 and C-6 C–H functionalization of indolines with azabenzonorbornadienes has been accomplished using Rh-catalysis. The reaction affords a potential route toward pyrrolocarbazoles with broad scope and functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…[32] Cui group reported the cyclization at the C7 and C6 positions of indolines using alkynes under Rh‐catalysis [32a] . While our group showed a one‐pot construction of pyrrolocarbazoles via Rh‐catalyzed site‐selective dual C−H activation of indolines at the C7 and C6 sites using azabenzonorbornadienes [32b] . Control experiments reveal that N ‐coordination is ideal for this reaction, while O ‐coordinating groups show no reaction.…”
Section: Functionalization Of C(7)−h Bondmentioning
confidence: 89%
“…[32] Cui group reported the cyclization at the C7 and C6 positions of indolines using alkynes under Rh‐catalysis [32a] . While our group showed a one‐pot construction of pyrrolocarbazoles via Rh‐catalyzed site‐selective dual C−H activation of indolines at the C7 and C6 sites using azabenzonorbornadienes [32b] . Control experiments reveal that N ‐coordination is ideal for this reaction, while O ‐coordinating groups show no reaction.…”
Section: Functionalization Of C(7)−h Bondmentioning
confidence: 89%
“…Shortly after this preliminary investigation, a follow-up study on pyrimidine directed synthesis of pyrrolocarbazoles was reported under Rh catalysis (Scheme 28). [89] Both protocols showed excellent functional group tolerance and a broad scope of 7-azabenzonorbornadienes as coupling components to deliver the desired adducts in good yields…”
Section: Annulation With Heterobicyclic Alkenementioning
confidence: 99%
“…An oxidative coupling reaction of N-substituted arylamides (11) with disubstituted alkynes (12) using Pd(OAc) 2 catalyst by Huang and co-workers also proceeded under basic conditions to generate N-substituted isoquinolones (13) (Scheme 4). [7] The reaction firstly proceeds via an oxidative insertion into a CÀ H bond in deprotonated substrates (11-A) that are generated from the reaction of 11 and base, using activated Pd(II) species to form Pd(II) intermediates (11-B).…”
Section: Transition Metal-catalyzed Retained Dual Functionalizationmentioning
confidence: 99%
“…Regarding Rh-catalyzed dual functionalization, a site-selective Rh-catalyzed dual CÀ H functionalization of N-(pyrimidin-2yl) indolines (26) with 7-azabenzonorbornadienes (27) to furnish pyrrolocarbazoles (28) was developed by Punniyamurthy and co-workers (Scheme 8). [12] A plausible reaction mechanism for the Rh-catalyzed dual CÀ H functionalization is shown as follows: the 2-pyrimidine group undergoes C(7)À H activation to form rhodacycles (26-A). Coordination of the rhodium center in 26-A with 27 gives Rh complexes (26-B), and 26-B undergo migratory insertion to yield CÀ C bond formed Rh complexes (26-C).…”
Section: Transition Metal-catalyzed Retained Dual Functionalizationmentioning
confidence: 99%